TEACHERS' RIGHT TO HEALTH IN THE POLICY DEBATES DURING THE COVID-19 PANDEMIC IN HUNGARY AND ROMANIA - Leyla SAFTA-ZECHERIA; Mihaela MITESCU MANEA; Eszter NEUMANN (National Centre for Policy and Evaluation in Education, 2022)
At the onset of the Covid-19 pandemic, governments worldwide suspended face-to-face education in schools to manage the spread of the Sars-Cov-2 virus. Romania and Hungary were not exceptional in this regard during the first wave of the pandemic. However, further along, the two countries' policy pathways strongly diverged. Hungary strategized keeping schools open to ensure parents could attend to their employment obligations. Romania suspended face-to-face education in schools for long periods. The paper looks at these two national cases through a Critical Frame Analysis (Dombos et al., 2012) of education policy debates during the initial three waves of the pandemic (March 2020 - July 2021). It answers the question: How were the health rights of teachers and the health crisis in education framed in the education policy debates during the Covid-19 pandemic? Policy documents and policy related position documents by non-government actors were selected by country experts from both countries and coded inductively looking at the right to education, the right to health, and the relationship between economic activities and education. We present our findings concerning how teachers' rights to health are featured in the policy debates between the government, oppositional political parties, trade unions and other stakeholders. Finally, we use our analysis to point to recommendations addressing the complex challenge of equally ensuring vulnerable pupils' rights to education and teachers' rights to health through coherent crisis management policies.